Interocular differences in choroidal thickness and circulation in anisomyopic adults and their association with myopia severity - Tang, Chong; Huang, Fanfan; Hu, Rong; Ji, Yan; Gao, Yu; Shi, Kai; Wu, Yuanyuan; Wan, Wenjuan (Frontiers in Medicine, 2025)
PurposeThe study aimed to compare interocular differences in choroidal thickness and circulation between the paired eyes of anisomyopic adults and to further investigate the potential connection between the choroid and myopia severity.MethodsA total of 120 eyes of 60 anisomyopic adults were included in this observational cross-sectional study. All patients underwent detailed ocular examinations, including spherical equivalent refraction (SER), axial length (AL), and other biometric parameters. Mean choroidal thickness (MCT), choriocapillaris blood flow area (CBFA), choroidal vessel volume (CVV), and choroidal vessel index (CVI) were measured over a 6 mm x 6 mm macular area using swept-source optical coherence tomography (SS-OCTA). Interocular differences in the abovementioned measurements between the paired eyes of the anisomyopic individuals were analyzed.ResultsThe mean SER was −5.98 ± 1.72 diopters (D) in the more myopic eyes and −3.38 ± 1.71 D in the less myopic eyes, while the mean interocular difference in SER was −2.60 ± 1.17 D. The more myopic eyes had lower values of MCT, CBFA, CVV, and CVI than the relatively less myopic fellow eyes (all p < 0.01). The interocular difference in SER was positively correlated with that in MCT, CVV, and CVI (all p < 0.05), and the interocular difference in AL was negatively correlated with that in MCT, CVV, and CVI (all p < 0.05). The multiple linear regression model with generalized estimating equations showed that the interocular difference in CVV was significantly associated with the interocular difference in SER (p < 0.05).ConclusionChoroidal thickness and circulation were found to be reduced in the more myopic eyes of anisomyopic adults. We observed that the greater the interocular difference in SER, the lower the choroidal thickness and circulation, indicating that the choroid is impaired in individuals with myopia and is more likely to be compromised with severe myopia.